2016
DOI: 10.1002/slct.201600125
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Mechanism of Epolactaene to Hsp60 Unveiled by in Silico Modelling

Abstract: Molecular Dynamics (MD) simulations and DFT/MM calculations were performed in order to rationalize available experimental results and to provide structural details on the binding mechanism of Epolactaene (EPO) to the 60 KDa Heat Shock Protein (Hsp60). The available crystal structure of Hsp60 represents the last step of the chaperone folding cycle, while the Hsp60-EPO complex was obtained by using a homology model of Hsp60, in order to simulate a state related to the beginning of the folding cycle (Rs1). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Epolactaene derivatives, such as the tertiary butyl ester ETB ( Figure 3 ), were also active [ 80 ] and SAR studies demonstrated that both the cyclic amide (lactam) and the α,β-unsaturated ketone are critical moieties for inhibiting the chaperone activity of Hsp60 [ 81 ]. An in-silico study suggested a putative mode of action for epolactaene, revealing the opening of a binding pocket in proximity of Cys442 after ATP occupies its binding site and that epolactaene covalently binds thiol moiety of Cys 442 through attack at C14 and epoxide ring-opening [ 82 ]. MD studies evidenced that epolactaene binding hinders the dynamic conformational changes of the monomer necessary for functional folding process.…”
Section: Hsp60mentioning
confidence: 99%
“…Epolactaene derivatives, such as the tertiary butyl ester ETB ( Figure 3 ), were also active [ 80 ] and SAR studies demonstrated that both the cyclic amide (lactam) and the α,β-unsaturated ketone are critical moieties for inhibiting the chaperone activity of Hsp60 [ 81 ]. An in-silico study suggested a putative mode of action for epolactaene, revealing the opening of a binding pocket in proximity of Cys442 after ATP occupies its binding site and that epolactaene covalently binds thiol moiety of Cys 442 through attack at C14 and epoxide ring-opening [ 82 ]. MD studies evidenced that epolactaene binding hinders the dynamic conformational changes of the monomer necessary for functional folding process.…”
Section: Hsp60mentioning
confidence: 99%
“…The transcriptional modifications, like S-guanylation in Cys 442 , can disturb the multichaperone complex stability and, therefore, alter the opening of the mitochondrial permeability pore 41 . In addition, covalent binding of metabolites like epolactaene or ETB (epolactaene tertiary butyl ester) to Cys 442 can induce the inhibition of HSP60 activity by disrupting oligomerization 28 or inducing conformational changes of the apical domain, responsible for the recognition of the co-chaperone HSP10 42 . In this sense, N-ethyl-maleimide or fluorescein-5maleimide modified the activity of HSP60 in steroidogenic cells by blocking cysteines through a thiol-maleimide reaction 27 that inhibits the protein activity by blocking cysteines 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the fact that myrtucommulone has other biological targets and, in addition to Hsp60, affects the arachidonic acid metabolism, this compound can provide a starting point for the development of analogs deprived of these activities [229]. Epolactaene, found in the fungal strain Penicillium sp., is another natural product reported to selectively inhibit Hsp60 activity through covalent binding to cysteine residues close to the ATP binding pocket, which indicates the allosteric regulation of Hsp60 without affecting its ATPase activity [230]. The folding activity of the Hsp60/Hsp10 complex can also be disturbed by curcumin in a dose-dependent manner, as reported in neuroblastoma cells [231].…”
Section: Hsp60-aimed Therapiesmentioning
confidence: 91%